2019
DOI: 10.1103/physrevb.100.115158
|View full text |Cite
|
Sign up to set email alerts
|

Theory of triangular lattice quasi-one-dimensional charge-transfer solids

Abstract: Recent investigations of the magnetic properties and the discovery of superconductivity in quasione-dimensional triangular lattice organic charge-transfer solids have indicated the severe limitations of the effective 1 2 -filled band Hubbard model for these and related systems. We present computational studies within the 1 4 -filled band Hubbard model for these highly anisotropic systems. Individual organic monomer molecules, and not their dimers, constitute the sites of the Hamiltonian within our theory. We f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 81 publications
(169 reference statements)
3
6
0
Order By: Relevance
“…In all lattices we find that as a function of λ,P reaches a broad peak at an intermediate value of λ before beginning to decrease. A similar broad maximum inP is seen as a function of U in zero temperature λ = 0 calculations at ρ = 0.5 [16,17]. We expect the decrease inP at larger λ and/or U is caused by the increasing effective mass of pairs.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…In all lattices we find that as a function of λ,P reaches a broad peak at an intermediate value of λ before beginning to decrease. A similar broad maximum inP is seen as a function of U in zero temperature λ = 0 calculations at ρ = 0.5 [16,17]. We expect the decrease inP at larger λ and/or U is caused by the increasing effective mass of pairs.…”
supporting
confidence: 55%
“…4) is very different from ρ = 1. At ρ ∼ 0.5 zero-temperature calculations find thatP increases with U [15][16][17]. Here, for all the lattices we find thatP increases with increasing U and λ at the same densities where T = 0 calculations find enhancement by U alone.…”
supporting
confidence: 51%
“…The U dependence of Figure 4e,f are harder to interpret. We believe that the unusual U dependence here is due to shorter range correlations, for example as in Figure 4b where P ⊥ (r) changes discontinuously at small U at r ∼ 2 [42]. As in Reference [41], as distances r < 3 are excluded, we again find a continuous decrease ofP ⊥ with increasing U.…”
Section: Resultssupporting
confidence: 78%
“…Pressure increases frustration, causing the spin singlets to be mobile. Calculations on an anisotropic triangular lattice [41] as well as on κ-lattices [42,57] have indeed found that superconducting pair correlations are enhanced by the Hubbard U uniquely at 1 4 -filling. DMRG calculations on a width-three triangular lattice found evidence for p-wave and d-wave SC in the density range 0.40∼0.65 [58], which would appear to agree with the conclusion from the previous work [41].…”
Section: Discussionmentioning
confidence: 92%
“…We believe that the unusual U dependence here is due to shorter range correlations, for example as in Fig. 4(b) where P ⊥ (r) changes discontinuously at small U at r ∼ 2 [41]. If distances r < 3 are excluded, we again find a continuous decrease of P⊥ with increasing U. Figs.…”
Section: Resultsmentioning
confidence: 52%